2010
DOI: 10.1037/a0016652
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation of the vulnerability of memory for positive and negative emotional scenes to the misinformation effect.

Abstract: This study examined (prospectively) the impact of the emotional content of visual scenes on memory accuracy and susceptibility to misinformation over time. After viewing a highly positive and highly negative photographic image, half of participants (N ϭ 80) were exposed to misinformation concerning the images and later responded to a series of questions about the details of each. After 1 week or 1 month, participants returned and were asked (unexpectedly) about the images. Overall, memories of misled participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 30 publications
(37 reference statements)
6
62
3
Order By: Relevance
“…That said, other studies have found that positive and negative scenes are well-remembered and less susceptible to change or misleading suggestions over time relative to neutral events (Brown and Schaefer 2010). These conflicting results may arise from methodological issues (i.e., measuring frequency relative to accuracy, how misinformation is calculated, varying levels of arousal associated with stimuli; Berntsen 2002; Van Damme and Smets 2014), failure to differentiate between central and peripheral details of events/scenes (e.g., Brown and Schaefer 2010;Porter et al 2010), and a lack of consideration of how individual differences influence susceptibility to misinformation (e.g., Zhu et al 2010). Our aim in this study was to address scene emotionality foremost, as well as personality factors that influence emotional processing.…”
Section: The Misinformation Effect and Emotionmentioning
confidence: 97%
See 4 more Smart Citations
“…That said, other studies have found that positive and negative scenes are well-remembered and less susceptible to change or misleading suggestions over time relative to neutral events (Brown and Schaefer 2010). These conflicting results may arise from methodological issues (i.e., measuring frequency relative to accuracy, how misinformation is calculated, varying levels of arousal associated with stimuli; Berntsen 2002; Van Damme and Smets 2014), failure to differentiate between central and peripheral details of events/scenes (e.g., Brown and Schaefer 2010;Porter et al 2010), and a lack of consideration of how individual differences influence susceptibility to misinformation (e.g., Zhu et al 2010). Our aim in this study was to address scene emotionality foremost, as well as personality factors that influence emotional processing.…”
Section: The Misinformation Effect and Emotionmentioning
confidence: 97%
“…The most common form of presentation of misinformation is through the use of leading questions, which generally result in false recollections of suggested details that were not present in the original scene/event (e.g., Ibabe and Sporer 2004;Porter et al 2010). Recent studies have turned their attention to examining misinformation in the context of scenes/events of differing emotional valence (e.g., Porter et al 2010;Van Damme and Smets 2014).…”
Section: The Misinformation Effect and Emotionmentioning
confidence: 98%
See 3 more Smart Citations